Nursing interventions in family health in families with elderly people with Alzheimer's: integrative review - Aya Roa, Kevin Julian (2022)
Objective: To identify the scientific evidence of nursing interventions in family health in families with older adults with Alzheimer's. Method: Integrative review in PUBMED, Scopus, Web of Science, Virtual Health Library (VHL), Springer Links and ScienceDirect databases, using the health sciences descriptors (DECS): Family Health, Aged, Alzheimer, Family Nursing and Controlled Before-After Studies; the Boolean operator AND was used to join the descriptors. Results: Five articles were found that addressed nursing interventions focused on the primary caregiver and nursing interventions focused on the family. Main results: Five articles were found within which nursing interventions focused on the main caregiver and nursing interventions focused on the family are addressed. Overall conclusion: Family health interventions may be directed toward the primary caregiver or the entire family and will likewise have some indirect effect on the elderly person with Alzheimer's disease.